A 210‐280 GHz balanced broadband tripler based on Schottky diode pair. Issue 3 (3rd December 2021) - Liu, Qiang; Fang, Yong; Mou, Cong; Liu, Jianlong; Zeng, Baoqing
Abstract: In this paper, a 210–280 GHz balanced broadband tripler based on a planar Schottky diode is designed and manufactured. Compared with the traditional tripler, the terahertz tripler adopts the modular design method of device and circuit combination and carries on the electromagnetic modeling of the diode according to the physical parameters of the diode. Combined with SPICE model simulation, it is conducive to accurately simulate the tripler. It has the characteristics of simple assembly, low loss, and stability. The reverse parallel diode pair is used as the core of the tripler to generate multiple harmonics, and the circuit is designed to obtain the required third harmonics. Under the condition that the input power is 5 dBm, the output power of the tripler is about −4.3 to −7 dBm in the frequency band of 210–280 GHz, and the bandwidth is about 28%. At 252 GHz, the output power is −4.3 dBm, and the conversion efficiency is about 11.7%, which is in good agreement with the simulation results.